Manter sadia a criança sadia: os preceitos higienistas veiculados na Revista de Educação de Goiás (1937-1962) - Viana, Verônica Pereira (2017)
This paper places itself in the History of Education, linked to the research field “State, Policies and History of Education” of the Graduate Program in Education of the Education School of the Federal University of Goiás. It is a historical research that uses the analytical strategy of the assumptions of cultural history, which proposes a renewal of objects and sources, as well as the way of approaching them, as recorded by Pesavento, Burke, Lopes and Galvão, among others. The main purpose of this study was to identify which guidelines and medical-hygienist prescriptions for the education of young children were published in the first six decades of the twentieth century. Our focus was the Goiás Journal of Education, a pedagogical publication of great importance to identify proposals and practices of regional and national educational history. The first step of the research was a bibliographical review of hygiene studies and their assumptions in Brazilian childhood education, from the second half of the nineteenth century until approximately the beginning of the second half of the twentieth century. Among the authors referenced are Gondra, Vigarello, Costa, Stephanou, Rocha, and others. Next, we contextualize the referential source of this research, the Goiás Journal of Education, composed of a series of 33 numbers, highlighting the continuities and discontinuities in the dissemination of educational, political and cultural issues, focusing on the diffusion of hygienist precepts. Regarding the use of pedagogical publications as a source in this field of research, we refer to Bastos, Luca, Biccas and others. Finally, we made a clipping of the articles of the journal, showing the diffusion of hygiene precepts aimed at the education of young children. Reaching the end of our research, we can say that the Goiás Journal of Education was one of the vehicles for the dissemination of hygienist precepts among the population of Goiás, and also that medical and hygienic actions aimed not only at health, but also at health education, focusing on the development of habits considered healthy from an early age, thus contributing to the construction of a hygienic culture in the state.